2010
DOI: 10.1089/ten.tea.2009.0546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ectopic Bone Formation of Embryonic Stem Cells and Cord Blood Stem CellsIn Vivo

Abstract: Cell-based reconstruction therapies promise new therapeutic opportunities for bone regeneration. Unrestricted somatic stem cells (USSC) from cord blood and embryonic stem cells (ESCs) can be differentiated into osteogenic cells. The purpose of this in vivo study was to compare their ability to induce ectopic bone formation in vivo. Human USSCs and murine ESCs were cultured as both monolayer cultures and micromasses and seeded on insoluble collagenous bone matrix (ICBM). One week and 1, 2, and 3 months after im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Handschel et al [43] reported that the combination of insoluble There are two main approaches to the design of support matrices. The first approach is the administration of large amounts of osteogenically predifferentiated cells in microsphere form [1,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Handschel et al [43] reported that the combination of insoluble There are two main approaches to the design of support matrices. The first approach is the administration of large amounts of osteogenically predifferentiated cells in microsphere form [1,36] .…”
Section: Discussionmentioning
confidence: 99%
“…The generation and expansion of USSC have also been compared with umbilical cord blood derived MSC (Kogler et al 2006). In a more recent study, the capacity of USSC for ectopic bone formation was also compared with embryonic stem cells (Handschel et al 2010). To the best of our knowledge, the osteogenic capacity of USSC has not been previously compared with BM-MSC and AT-MSC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study compared cord blood mononuclears with ESCs in regard to their ability to produce ectopic bone following intramuscular implantation of differentiated stem cell-collagen constructs. They found that UCB mononuclears were superior to ESCs, from the first post-implantation month, in terms of mineralization [60]. Moreover, it has been shown that osteogenesis in UCB-MSCs is feasible and is maximized when MSCGM (a commercial growth medium containing DMEM and FCS) conditioned with 10% SingleQuot and dexamethasone in a concentration of 10 --7 M is utilized for the differentiation [61].…”
Section: Bone Tissue Regenerationmentioning
confidence: 99%
“…CT scans were performed at the end of each month for 3 months and specimens were histologically examined Ten times higher mineralization was seen in UCBMSC than in ESC constructs UCBMSCs are better than ESCs in inducing in vivo ectopic bone formation when combined with insoluble collagenous bone matrix scaffolds [60] Hildebrandt et al MSCGM medium with 10% SingleQuot was better at supporting differentiation UCBMSCs differentiate more effectively into the osteogenic lineage when cultured with MSCGM with 10% SingleQuot and 10 --7 M dexamethasone [61] Bosch et al [63] Unless stated otherwise, osteogenesis was induced with classic osteogenic medium containing dexamethasone, b-glycerophosphate and ascorbic acid, for 21 days. suitable for bone regeneration purposes [62].…”
Section: Bone Tissue Regenerationmentioning
confidence: 99%